A label-free RTP sensor based on aptamer/quantum dot nanocomposites for cytochrome c detection. Issue 55 (8th October 2019) - Li, Dongxia; Guo, Junping; Zhao, Liang; Zhang, Guoxian; Yan, Guiqin
Abstract : In this study, the nanocomposites from polyethyleneimine-capped Mn-doped ZnS QDs (PEI-QDs) and Cyt c binding aptamer (CBA) were prepared and used as Cyt c RTP sensors.. Abstract : Given the outstanding room-temperature phosphorescence (RTP) of Mn–ZnS quantum dots (QDs) and the specific recognition performance of the aptamer, we built phosphorescent composites from aptamers conjugated with polyethyleneimine quantum dots (PEI-QDs) and applied them to cytochrome c (Cyt c ) detection. Specifically, QDs/CBA composites were generated from the electrostatic interaction between the positively-charged PEI-QDs and the negatively-charged Cyt c binding aptamer (CBA). With the presence of Cyt c, the Cyt c can specifically bind with the QDs/CBA composites, and quench the RTP of QDs through photoinduced electron-transfer (PIET). Thereby, an optical biosensor for Cyt c detection was built, which had a detection range of 0.166–9.96 μM and a detection limit of 0.084 μM. This aptamer-mediated phosphorescent sensor with high specificity and operational simplicity can effectively avoid the interference of scattering light from complex substrates. Our findings offer a new clue for building biosensors based on QDs and aptamers.